Organoleptic Test of Instant Lemongrass-Ginger Tea Bags as a Local Herbal Beverage Product of Kedungbanjar Village, Sugio, Lamongan - Sofia, Diana; Pribadi, Eko Teguh; Kusumawati, Estri; Andiarna, Funsu (International Conference on Sustainable Health Promotion, 2025)
Background: Lemongrass and ginger tea is a traditional herbal drink that has health benefits and the potential to be developed as a local product. Objective: This study aims to assess the level of public acceptance of lemongrass-ginger tea bags in Kedungbanjar Village, Sugio District, Lamongan Regency. Methods: This study used a descriptive analytical design with a cross-sectional approach through organoleptic testing of 48 housewife respondents. The assessment was carried out on the aspects of taste, aroma, color, and packaging appearance using a 1–5 Likert scale. Result: The results showed that the taste aspect received an average score of 3.7 (like), aroma 3.9 (like), color 3.4 (like), and packaging appearance 4.1 (like). Overall, this product was well received by respondents due to its practicality, consistent taste, and health benefits from the bioactive compounds in lemongrass and ginger. However, the color aspect still needs improvement, flavor variations need to be added, and the packaging design needs to be enhanced to increase the product’s appeal. With further development, lemongrass-ginger herbal tea has the potential to become a healthy local herbal drink with economic value